Keefektifan Teknik Behavior Cont Keefektifan Teknik Behavior Contract Dalam Bingkai Konseling Kelompok Behavioral Untuk Mereduksi Prokrastinasi Akademik Siswa - Krismi; IM. Hambali; Diniy Hidayatur Rahman (Universitas Nusantara PGRI Kediri, 2021)
Academic procrastination was are commonly found in many schools. It is proved by the result of survey in SMPN 1 Kesamben, Blitar which showed 53% of students did academic procrastination. One of the effective counseling techniques to reduce academic procrastination is behavior contract through behavioral group counseling. This study aimed to test the effectiveness of Behavior Contract technique through behavioral group counseling to reduce students' academic procrastination. This Study used One Group Pretest-Posttest design. The subjects of the study were 6 students found by purposive sampling. The research data was collected by academic procrastinations scale. The data analysis result using Wilcoxon Signed Rank Test showed the score of asymp.sig.(2-tailed) equal to 0.028. Those result indicated that behavior contract technique through behavioral group counseling was effective to reduce students' academic procrastination.